Using Elf Strategies in Teaching Students Who Speak Bilingual/Multilingual in the Classroom - Triana Ina Weran, Yohana; Sa’adah, Lailatus (International Journal of Education and Digital Learning (IJEDL), 2023)
This study is aimed to show the implementation of English as a lingua franca in elementary school students. The researchers would like to present the strategies used by the teachers in teaching some subjects to students who barely speak Indonesian. This study has not been discussed by many researchers. The use of the ELF strategy by teachers in teaching subjects in a classroom is to keep students engaged in the topic that is being discussed. The researchers employed qualitative research involving five teachers who taught English, Indonesian, and also class teachers in the elementary school. In collecting the data, the researchers participatory sampling and open-ended questions for the participants. In this research, 4 classes have several students who can speak more than one language but are not too fluent in Indonesian. The result of the study showed that teachers used some techniques to teach the students such as using repetition and paraphrasing, code-switching, using pictures, and help-seeking. Moreover, the researchers also found that through the strategies implied by the teacher, students could grasp the material taught by the teacher easily.